2019
DOI: 10.35940/ijitee.l3369.1081219
|View full text |Cite
|
Sign up to set email alerts
|

Do Work Experience, Good Governance, and Independence Influence the Audit Quality?

Abstract: Financial auditors play an important role in the financial reporting of business entities. The auditor must examine the report or bookkeeping company. When conducting its audit work, auditors are required to have competence in accounting or finance and always maintain an independent attitude. Even so, until now there are still many people who doubt the competence and independence of public accountants. This is compounded by the many cases involving the public accounting profession, in many financial statement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
1
0
4
Order By: Relevance
“…Research related to the effect of work experience on audit quality was achieved by Meini et al (2022) andZamzami et al (2017), which obtained the result that work experience affects audit quality. However, there are different results in the research conducted by Handoko et al (2019), work experience does not affect audit quality. Albertoaran conducted subsequent research on the effect of organizational commitment on audit quality (2022), and Mardika & Suartana (2019), concluded that organizational commitment positively impacts audit quality.…”
Section: Introductionmentioning
confidence: 87%
“…Research related to the effect of work experience on audit quality was achieved by Meini et al (2022) andZamzami et al (2017), which obtained the result that work experience affects audit quality. However, there are different results in the research conducted by Handoko et al (2019), work experience does not affect audit quality. Albertoaran conducted subsequent research on the effect of organizational commitment on audit quality (2022), and Mardika & Suartana (2019), concluded that organizational commitment positively impacts audit quality.…”
Section: Introductionmentioning
confidence: 87%
“…Penelitian ini memberikan makna bahwa semakin berpengalaman seorang auditor akan semakin optimal kinerjanya, karena lebih mampu mendeteksi dan menemukan penyebab dari terjadinya kecurangan (fraud), oleh karena itu kualitas audit akan memiliki kualitas dibandingkan dengan auditor yang tidak memiliki pengalaman. Hasil penelitian sejalan dengan penelitian yang dilakukan oleh Dewi, et al, (2019) dan Putri (2020), namun tidak sejalan dengan penelitian Handoko, et al, (2019).…”
Section: Pembahasan Penelitian Pengaruh Pengalaman Auditor Terhadap K...unclassified
“…Dan juga berdasarkan penelitian sebelumnya yang dilakukan oleh Widiastuti (2016) dan Hafizh (2017) menyatakan bahwa pengalaman kerja berpengaruh signifikan terhadap kualitas audit. Sedangkan penelitian yang dilakukan oleh Atmaja (2017) dan Handoko et al (2019) menyatakan bahwa pengalaman kerja tidak berpengaruh signifikan terhadap kualitas audit. Hal ini menunjukkan bahwa masih terjadi GAP riset sehingga variabel Kompetensi dan Pengalaman Kerja akan diteliti kembali pada penelitian ini.…”
Section: Synergyunclassified
“…Hasil penelitian ini sejalan dengan penelitian sebelumnya yang dilakukan oleh Anggrainy (2017) dan Tobing (2016) yang menunjukkan bahwa pengalaman kerja berpengaruh signifikan terhadap kualitas audit. Hasil penelitian ini tidak sejalan dengan penelitian yang dilakukan oleh Atmaja (2017) dan Handoko et al (2019) yang menunjukkan bahwa pengalaman kerja tidak berpengaruh signifikan terhadap kualitas audit.…”
Section: Pengaruh Pengalaman Kerja Terhadap Kualitas Auditunclassified
See 1 more Smart Citation